Assessment of efficacy and effectiveness of some extracted bio-chemicals as bio-fungicides on wood : Procjena učinkovitosti i djelotvornosti ekstrahiranih biokemikalija kao fungicida za drvo - Salem, Mohamed Z. M. (Array, 2019)
The present study investigates in-vitro the antifungal activity of two extracts (ethyl ether extracts of Schinus terebinthifolius ripened fruits and Pinus rigida heartwood) and two essential oils (Thymus vulgaris and Origanum majorana leaves) against two species of fungi; Trichoderma harzianum and Aspergillus niger. The results clearly show that O. majorana oil and P. rigida wood extract had the highest activity against both fungi and were chosen for the application on four wood species; Weeping-Wreath Wattle (Acacia saligna), Beech (Fagus sylvatica), Black Walnut (Juglans nigra) and Pitch Pine (Pinus rigida). Additionally, their impact on the wood structure was examined by FTIR, SEM and colorimetry. The study suggests that O. majorana oil appears to show the best results and could be used as friendly bio-fungicides to protect wood objects without changing their structures.